Management of pneumothorax in the setting of chronic non-invasive positive pressure ventilation: A case series. (2022) - Kumar, Avnee J.; Hjelmaas, Alexander; Singer, Benjamin H.
Abstract: There is a growing population of patients who require chronic noninvasive ventilation. While these patients often have no parenchymal lung disease, the use of positive pressure ventilation itself predisposes to both initial and recurrent pneumothoraces. Furthermore, generally accepted pneumothorax management strategies, such as removing a chest tube after liberation from positive pressure ventilation, are not possible in this population. Despite this, there is a lack of clear guidance on management of pneumothorax in the chronically ventilated patient. In this case series, we discuss the management of pneumothoraces in patients requiring chronic noninvasive mechanical ventilation in our Assisted Ventilation Clinic (AVC). Our experience suggests a potential role of definitive treatment of the initial pneumothorax to prevent reoccurrence.